ANALISIS HUKUM DAN KEBIJAKAN DALAM PENANGGULANGAN PERDAGANGAN ORANG DI INDONESIA - Muliadi, Muliadi; Adnan, Idul (AL-BALAD : Jurnal Hukum Tata Negara dan Politik Islam, 2024)
This research aims to analyze human trafficking, which is a form of transnational crime that continues to increase in Indonesia, even though various legal and policy efforts have been taken to tackle it. This study aims to analyze the driving factors behind the crime of human trafficking and identify the challenges facing the implementation of countermeasures policies in Indonesia. The two problem formulations that are the focus of this research are: first, what are the factors that encourage the crime of human trafficking in Indonesia? Second, what challenges are faced in implementing policies to combat human trafficking in Indonesia? The results of this research show that the main driving factors include poverty, low levels of education, gender inequality, and weak law enforcement. In addition, the main challenges in implementing policies include less than optimal coordination between institutions, limited resources, and cultural and social barriers. Based on these findings, a holistic and synergistic approach is needed between the government, society and international institutions to increase the effectiveness of combating human trafficking in Indonesia.